Islas Flotantes Artificiales con Vetiver (vetiveria zizanioides) como alternativa para la remoción de Nitratos, Fosfatos y Plomo en Agua procedente del Río Cutuchi - Herrera Toapanta, Viviana Nataly (2019)
Artificial floating islands are a system of phytoremediation of polluted water, similar to natural wetlands. The objective of this research was to evaluate the effect of the Vetiver (V. zizanioides) species in the removal of NO3, PO4 and Pb in water from Cutuchi River. For this purpose, a floating island of 0.09 m2 was installed in a volume of water of 115 liters (treatment 1), three repetitions and a witness. Evaluations of the removed parameters were every 21 days and every seven days of the development of the plant during four months. The removal percentages were: nitrates 82,11%, phosphates lead 99,72% and 50%. The system with V. zizanioides varieties constitutes an alternative to improve water quality.